Abnormal Regional Spontaneous Brain Activity and Its Indirect Effect on Spasm Ratings in Patients With Hemifacial Spasm - Luo, Fei-Fei; Xu, Hui; Zhang, Ming; Wang, Yuan (Frontiers in Neuroscience, 2020)
Purpose: Three classical methods of resting-state functional magnetic resonance imaging (rs-fMRI) were employed to explore local functional abnormalities and their effect on spasm ratings in hemifacial spasm (HFS) patients. Methods: Thirty HFS patients and 30 matched healthy controls (HCs) were recruited. Rs-fMRI data, neurovascular compression (NVC) degree and spasm severity were collected in each subject. Fractional amplitude of low-frequency fluctuation (fALFF), regional homogeneity (ReHo), and degree centrality (DC) were calculated in the whole brain voxels. Two sample t-tests were performed to investigate group differences of fALFF, ReHo, and DC. Correlation analysis was performed to assess the relationships between the regional brain abnormalities and clinical variables in HFS. Results: Compared with HCs, HFS patients exhibited increased fALFF in the left precuneus and right posterior cingulate cortex (PCC), together with increased ReHo in the bilateral PCC and bilateral precuneus. Decreased ReHo was observed in the right middle occipital gyrus (MOG), right superior occipital gyrus (SOG), right cuneus, and right angular gyrus (AG) in HFS patients. Moreover, ReHo in the right PCC were positively correlated with NVC degree and spasm severity in HFS patients, respectively. Mediation analysis revealed that increased ReHo in the right PCC regulated the neurovascular compression degree, and further resulted in increased spasm ratings. Conclusion: Our study revealed regional brain dysfunctions from different perspectives and an indirect effect of ReHo in right PCC on spasm ratings predominantly through the alteration of NVC.